2015
DOI: 10.1007/s10008-015-2997-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of electrochemical performances of carbon nanomaterial-modified electrodes for DNA detection. Nanotubes or graphene?

Abstract: Artículo de publicación ISIA comparative study about the electrochemical response of glassy carbon electrode modified with four different carbon nanomaterial (CNM) against dsDNA is reported. The CNM used were oxidized and nonoxidized multiwalled carbon nanotubes (MWNT-OX and MWNT, respectively), graphene oxide (GO) and chemically reduced graphene oxide (RGO) and dispersed in 3:1 chitosan/water mixture. The electrodes were characterized by cyclic voltammetry, scanning electrochemical microscopy, and contact ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The best current response using TRGO was observed independently of the accumulation times (inset Figure 6 ), and the same behaviour was observed for the oxidation potential (not shown). In a previous study, we compared the effect of using carbon nanotubes or graphene, either oxidized or reduced, on the electrochemical behaviour of double strand DNA (dsDNA), and no potential shift was observed when oxidized and non-oxidized multi-walled nanotubes (MWNT, MWNT-OX), and a commercially available chemically reduced GO were used; furthermore, when GO was used, a 40 mV more positive potential shift was observed [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best current response using TRGO was observed independently of the accumulation times (inset Figure 6 ), and the same behaviour was observed for the oxidation potential (not shown). In a previous study, we compared the effect of using carbon nanotubes or graphene, either oxidized or reduced, on the electrochemical behaviour of double strand DNA (dsDNA), and no potential shift was observed when oxidized and non-oxidized multi-walled nanotubes (MWNT, MWNT-OX), and a commercially available chemically reduced GO were used; furthermore, when GO was used, a 40 mV more positive potential shift was observed [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several studies about DNA biosensors have been reported for GO [ 25 , 26 , 27 ] and RGO [ 28 ], but no comparison between the GO/RGO materials was performed. In a previous work, we demonstrated that CRGOs show clear electrochemical improvement compared to GO when used against dsDNA oxidation [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, evaluation of the intensity of this process is of great importance, in particular for environmental monitoring of genotoxic compounds [ 53 ]. Nanomaterial-modified electrodes can provide very simple and sensing platforms for DNA electroanalysis [ 54 , 55 ]. The developed GrO-IL-AuNPs-Chit/CSE was found to have excellent adsorption ability and electrocatalytic activity towards the irreversible oxidation of the fish sperm ds-DNA in aqueous solutions (pH 7.4).…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is compatible with a negative feedback between the tip and the substrate, indicating that GO blocks the electrochemical response of the FcOH redox mediator. This result is in agreement with that reported by us in a previous study in which chitosan was used as dispersing agent instead of water . When GO was electrochemically reduced to erGO (−1.000 V for 120 s), the conductive response of erGO/GCE improved (Figure C, b).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning carbon‐based nanomaterials, single and multiwalled nanotubes have attracted considerable attention because this material has presented better electroactivity toward the oxidation of some biomolecules, such as ascorbic acid, uric acid, and dopamine, over other types of carbon allotropes . However, graphene derivatives, which consist of a single atomic layer of hybridized carbon sp 2 that can be functionalized with oxidative moieties generating graphene oxide (GO) or with these functional groups reduced, generating reduced graphene oxide (rGO), have been successfully used to improve the electron transfer of many biological molecules . rGO can be generated by the reduction of GO through four main routes and shown a better electrochemical response for several biological molecules compared to GO .…”
Section: Introductionmentioning
confidence: 99%